Pemahaman Ilmu Tajwid terhadap Kemampuan Membaca Al-Qur’an di Pondok Pesantren Al-Falah Sumberadi Kebumen - Puput Apriyanti; Eliyanto Eliyanto (Prodi Pendidikan Agama Islam IAINU Kebumen, 2023)
This research is motivated by the importance of understanding the science of recitation on the ability to read the Koran in students. In this regard, this study aims to determine the understanding of the science of recitation, determine the ability to read the Koran, and know the methods of learning recitation. This research is a qualitative research. data collection through interviews, observation, and documentation. data analysis techniques include data reduction, data presentation, and drawing conclusions. his research resulted in three conclusions, namely: (1)The understanding of tajwid science by female students of the sifir class and 1 ibtida of the Al-Falah Islamic Boarding School Sumberadi Kebumen is good. It's not all, but on average already understand everything. After the oral test was carried out on female students in the sifir and 1 ibtida classes, there were some students who still mistakenly stated the law of reading recitation, and there were those who said wrongly the letters included in the law of reading. However, even though there are still mistakes, on average the female students of the sifir and 1 ibtida classes understand everything. (2) The ability to read the Al-Qurán for female students of the sifir class and 1 ibtida of Al-Falah Islamic Boarding School Sumberadi Kebumen is on average all fluent. The problem is that there are some students who already know the law of recitation but do not apply it when reading the Al-Qur'an, there are also students who read it in a hurry, even though reading the Al-Qur'an properly and correctly is not judged by how fast it is, but whether it is appropriate or not when read the Al-Qur'an with the rules of tajwid science. (3) The methods used in learning tajwid science at the Al-Falah Islamic Boarding School Sumberadi Kebumen are the lecture method, the discussion method, and the sorogan method. The lecture method is the delivery of material by the teacher orally to the students. The discussion method is the method in which the students discuss what is ordered by the teacher, such as looking for reading laws in a letter. The sorogan method is where the students come forward one by one reading the Qur'an to the teacher by applying the science of recitation. If wrong immediately corrected by the teacher.